Umbilicoportography - Davidenko, Nicolás; Casanova, Marys A (Cirugía del Uruguay, 1973)
The paper contains a brief summary of the anatomy of the umbilical vein and the technique employed in its repermeation. The procedure is simple and inocuous. It is used as approach to the portal system umbilicoportógraphiesa and oleohepatographies, thus avoiding the "splenic macula". The method was employ.ed on 13 patients, successfully in 10, the remaining 3 being failures.